Itching for nail fashion: chronic urticaria and chronic hand dermatitis secondary to acrylate and methacrylate allergy in gel nail varnish. (23rd October 2017) - Dickison, P.; Smith, S. D.
Summary: Allergic contact dermatitis (ACD) secondary to acrylates and methacrylates is a well‐ described occurrence, particularly in those who wear or handle gel nail varnish. Management involves avoidance of the identified allergen. The cause of chronic urticaria (CI) is often not identified, and CU is not known to be associated with acrylates or methacrylates. We report a case of a 50‐year‐old woman who initially presented with hand dermatitis exacerbated by gel nail varnish on a background of CU. Avoiding all nail varnishes because of her ACD also resulted in improvement of her CU. To our knowledge, this is the first documented case of CU secondary to the acrylates and methacrylates found in nail cosmetics.